'Our aim is to assist migrants in making a well-informed decision': how return counsellors in Austria and the Netherlands manage the aspirations of unwanted non-citizens. Issue 17 (5th October 2021) - Cleton, Laura; Schweitzer, Reinhard
ABSTRACT: European governments widely celebrate and extensively fund 'assisted voluntary return' (AVR) programmes and assume that return counsellors play an important role for their implementation. At the same time, relevant legislation only vaguely defines this role and reduces it to a passive and neutral provision of 'objective information'. In this article, we therefore ask how much and what kind of agency individual counsellors exercise and how this affects the aim and nature of AVR. We argue that counsellors fulfil a highly ambiguous function within a system that overall aims to bring unwanted migrants' decision-making in line with restrictive immigration law. This function requires considerable autonomy to choose and use the various kinds of information they provide. We conceptualise their work as 'aspirations management' that mediates the 'asymmetrical negotiation' between precarious status migrants and the governments seeking to deport them. Based on original qualitative data from Austria and the Netherlands, we analytically distinguish three fundamentally different counselling strategies: facilitating migrants' existing return aspirations, obtaining their compliance without aspirations, and/or inducing aspirations for return. This framework not only helps us to conceptualise AVR counsellors' specific agency, but will also be useful for analysing how other actors manage the aspirations of unwanted non-citizens.